Rear view of house at Shortlands, one of Henry Handel Richardson's homes, Queenscliff, Victoria, approximately 1912. (1912)
Rear view of house at Shortlands, one of Henry Handel Richardson's homes and featured in her writing, Queenscliff, Victoria, ca. 1912.
Title devised from caption list.
Condition: Creases and yellowing.
Part of the collection: Collection of Henry Handel Richardson photographs.
Inscriptions: "The house from the back at Shortlands."--In pencil on reverse.
Also available online
Donated by Dorothy Green.
Keywords: Richardson, Henry Handel, -- 1870-1946 -- Homes and haunts -- Photographs; Dwellings -- Victoria -- Queenscliff -- Photographs; Queenscliff (Vic.) -- Buildings, structures etc. -- Photographs